Full-color enhanced second harmonic generation using rainbow trapping in ultrathin hyperbolic metamaterials - Junhao Li (Nature Portfolio, 2021)
Though metamaterials enhance nonlinear light-matter interactions due to their resonant features, these materials typically show a narrow spectral bandwidth. Here, the authors report broadband enhanced second-harmonic generation in patterned multilayer hyperbolic metamaterial arrays.